(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aims: Acute kidney injury (AKI) is described as an abrupt and generally reversible damage of renal function that occurs over days or weeks. Nearly 20% of nephrotoxicity is associated with the use of antimicrobials and antibiotics. Materials and Methods: The evaluation of the possible protective effect of MnO nanoparticles (NPs) as well as explore their toxic effects on the kidneys of rat models. MnO NPs were prepared and evaluated for their physicochemical properties. The effect of MnO NPs was compared with gentamicin. Results and Discussion: In vivo data showed no toxicity according to zootechnical parameters, blood biochemistry, and organ system toxicity in MnO NP treatment groups. The protective effect of the MnO NPs group as compared to the gentamicin treatment group was observed. Conclusion: Hence, using the MnO NPs will help improve the AKI values.